Variable Speed Pumped Storage Hydropower Generation - Dhyani, Ashish; Kumar, Abhishek; Lamba, Rishabh; Rajora, Rohit Kumar; Chaudhary, Vishal (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2014)
The potential advantages of variable speed hydroelectric generation are discussed in this paper. Some general aspects concerning the efficiency gains in turbines and the improvements in plants operation are analysed. The main results of measurements done on a test loop with an axial-flow turbine are reported. Also is described the control scheme implemented, which is based on artificial neural nets (ANN). The conclusions encourage the realisation of more detailed studies, especially for low head plants, in order to confirm the practical interest of this technology.